Empreendedorismo: habilidade para indiv??duos e pr??tica para organiza????es - Pereira, Bruno Castilho Barbosa (2016)
Profit, growth, stability and social recognition are things that organizations desire. They also want competent and committed employees who can work in groups. In this sense, the challenges are numerous because, in general, companies are affected by problems caused by project delays, processes or systems failures, technical knowledge not distributed, communication problems, changing priority, employee severance, goals not reached, among others. In addition, so that the relationship between the company and the employee is not limited to the employment deal, there must be a well-defined strategy to awaken this desire contributor of growth, providing a favorable environment for such. Given this complex scenario, organizations and their employees can be supported with the existing knowledge about entrepreneurship in an approach that allows for their application in the business environment. The opportunity perceived in this research is directed to the study of entrepreneurial practices and how they could be used strategically as a response to organizational challenges related to project management, offering proposed actions to companies and their employees achieve better results.